ANALYSIS OF VARIATION OF WIRE FEEDER SPEED ON GMAW WELD PROCESS AGAINST MICRO AND STRUCTURE VIOLENCE ASTM STEEL A36 - Aditya Nur Ramadhan M.Ngari.SR.; Mastiadi Tamjidillah (Scientific Journal of Mechanical Engineering Kinematika, 2020)
This study aims to determine the effect of variations in wire feeder speed on the GMAW welding process on the hardness and microstructure of ASTM A36 steel. Wire feeder variations used are 3.5 meters / minute, 3.55 meters / minute and 3.6 meters / minute, ER 70S-6 electrodes with a diameter of 1.2 mm. The results showed that the highest hardness value in weld metal was found in specimen 1 wire feeder speed of 3.5 meters / minute with hardness value of 59.5 HRB. The highest hardness value in the HAZ area is in specimen 3 with a wire feeder speed of 3.6 meters / minute with a hardness value of 57.5 HRB. While the highest base metal hardness value is in the specimen 3 wire feeder speed of 3.55 meters / minute with a hardness value of 64.4 HRB. Microstructure observation results show that the higher the hardness value will increase the pearlite phase more and vice versa the lower the hardness value the ferrite phase is more than the pearlite phase.